2011
DOI: 10.1002/cbdv.201000348
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships of the Genus Chamaecyparis Inferred from Leaf Essential Oil

Abstract: The species differentiation between Chamaecyparis formosensis, C. obtusa var. formosana, and C. obtusa, based on the composition of the leaf essential oils, was studied. The characterization of the oils by GC-FID and GC/MS analyses showed remarkable differences between these three essential oils. Cluster analysis (CA) and principal-component analysis (PCA) distinguished three groups of essential oils. The C. formosensis oil was dominated by α-pinene while those isolated from C. obtusa var. formosana and C. obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 39 publications
(45 reference statements)
7
15
0
Order By: Relevance
“…There have been many research reports on the components of the typical taxon, C. obtusa [1,2,3,4], along with other reports that have examined the antibacterial and antifungal activity [5][6][7][8]. While in Japan it has been suggested that the essential oil from C. obtusa (EOCO) may have a relaxing effect, there have yet to be any detailed reports on this.…”
mentioning
confidence: 99%
“…There have been many research reports on the components of the typical taxon, C. obtusa [1,2,3,4], along with other reports that have examined the antibacterial and antifungal activity [5][6][7][8]. While in Japan it has been suggested that the essential oil from C. obtusa (EOCO) may have a relaxing effect, there have yet to be any detailed reports on this.…”
mentioning
confidence: 99%
“…As for the essential oils of Cof, sesquiterpene hydrocarbons and oxygenated sesquiterpenes constituted the major fractions; while monoterpene hydrocarbons and oxygenated monoterpenes accounted for the largest fractions in the oils of Co. 7 Taken as a whole, the essential oil components found in Cof and Co had higher proportion of polar compounds, and their molecular weights were higher than those of compounds found in Cf. The reason that Cof and Co have higher boiling points than Cf might be the additional energy required to break the hydrogen bonds for vaporization of the molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…These were in agreement with the constituents in leaf essential oils. 7 As for the VOCs of leaves collected from Mt. Chilan, sesquiterpene hydrocarbons (74.96%) constituted the major fraction, while sesquiterpene hydrocarbons (57.03%) and monoterpenoids hydrocarbons (32.04%) accounted for the largest fraction in the VOCs of leaves collected from Neimaopu.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chamaecyparis obtusa (CO), commonly known as hinoki , belongs to the Cupressaceae family, and it is grown in China, Japan, and the Republic of Korea [1,2,3]. CO lumber has been used widely in the manufacture of bathtubs, furniture, and pillow stuffing material, and as a source of CO oil.…”
Section: Introductionmentioning
confidence: 99%